Pendampingan Optimalisasi Perhitungan HPP dengan Metode FIFO untuk PT. Pesuntani Pekanbaru - Candra Irawan; Zubir; Menhard (Edujavare Publishing, 2024)
In the MSME business world, it is very necessary to have a strong desire, patience, perseverance and sincerity for all efforts undertaken in order to achieve the desired results and provide the best results in the future. The method used in community service is the interview method for collecting primary data and the lecture method in explaining the cost of goods sold. To start a business, you need skills and mature planning, so that the business you run can be in accordance with your wishes in the future. Based on the the cost of goods sold calculations carried out, it can be concluded that the the cost of goods sold for 2023 is 26,558,962.50